Valoración económica calidad del aire barrio “Los Pinos” cantón Riobamba, provincia de Chimborazo, periodo 2021. - Toalombo Pilamunga, Jonathan Fernando (2022)
The present research work focuses on analyzing the determining factors to accept economic compensation by the inhabitants of the "Los Pinos" neighborhood in the Riobamba canton, Chimborazo province, for which it is important to highlight an adequate application of the Contingent Valuation Method. (MVC), in this context, the concise definition of property rights is important, that is, to assess the benefits of an improvement in environmental quality about the monetary amount that the beneficiaries of that improvement would be willing to receive or pay. In this way, an assessment of the costs generated by environmental damage is measured through the amount of money on the resource to be assessed. The willingness to accept (DAA) is admitted by the individuals who are immersed in the case study if it implies improvements in the quality or quantity of the environmental resource (air) and only if the utility generated after making the payment is greater than or equal to the utility currently perceived without the environmental improvement. On the other hand, it allows determining the minimum willingness to receive, that is, monetary compensation for the relationship that occurred in the quality of the resource (air), assuming a decrease in well-being due to less availability or a drop in its environmental quality. For the analysis of results, the contingent valuation method was applied, where it was obtained the variables that represent the greatest significance in the investigation were: age, marital status, level of education, income level, and the monthly amount paid is spent on medicines and medical care for respiratory conditions, later the logistic regression econometric model (LOGIT) was formulated where it was possible to estimate that an individual is willing to accept monetary compensation for environmental damage when their income level ranges between 400.00 and 600.00 dollars. Finally, the conclusions and recommendations of the research work will be established.